2022
DOI: 10.1186/s12920-022-01316-7
|View full text |Cite
|
Sign up to set email alerts
|

High expression of serine and arginine-rich splicing factor 9 (SRSF9) is associated with hepatocellular carcinoma progression and a poor prognosis

Abstract: Background Serine and arginine-rich splicing factor 9 (SRSF9) has been linked to the occurrence and progression of various cancers; however, its effects and mechanism of action hepatocellular carcinoma (HCC) have not been reported. In this study, we used a bioinformatics approach and in vitro assays to evaluate the expression of SRSF9 in HCC, its prognostic value, and its underlying regulatory mechanisms, including analyses of related pathways and the role of methylation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…SRSF9 has also been implicated in cancers like hepatocellular carcinoma [22], colorectal cancer [23], and cervical cancer [24]. Frequent upregulation of SRSF10 in oral cancer has also been described earlier and it may have a role to play in its oncogenesis [25].…”
Section: Resultsmentioning
confidence: 78%
“…SRSF9 has also been implicated in cancers like hepatocellular carcinoma [22], colorectal cancer [23], and cervical cancer [24]. Frequent upregulation of SRSF10 in oral cancer has also been described earlier and it may have a role to play in its oncogenesis [25].…”
Section: Resultsmentioning
confidence: 78%
“…Five datasets in this sample actually doubled their peak numbers after the inclusion of Allo including BRCA1, a well-known tumor suppressor gene 26 . In analyzing repetitive element family associations (Figure 7C), we also identified other TFs involved in cancer progression, including Jun 27 , ILK 28 , SRSF9 29 , and NCOA2 30 , that are highly associated with particular repeat families. Outside of Jun, none of these TFs have been previously identified as binding to repetitive elements.…”
Section: Discussionmentioning
confidence: 95%
“…SR proteins were found to regulate all levels of gene expression via transcription initiation and elongation, alternative splicing, mRNA stability, translation, and protein degradation [ 28 ]. The roles of SRSF9 were different in various pathologic-clinical subtype in cancer [ 29 30 31 ]. Recent pan-cancer analysis revealed that SRSF9 was upregulated in the proliferative subtype of OC and downregulated in the mesenchymal subtype of OC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%